ANALISA STRUKTUR ALIRAN PADA TURBIN AIR UNDERSHOT TIPE SUDU DATAR UNTUK ALIRAN PADA SUNGAI KECIL - Febrizal, Febrizal; Asral, Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research was taken cause lack of potential energy use on water turbine with low head. In this research is done flow structure analysis on undershot water turbine flat blade type with variations of water level refers to the results that have been done. This research has purpose to obtain flow structure such as pressure distribution and water velocity vector around the water turbine blades. In the modeling of geometry design Autodesk Inventor 2016 was used and simulated by ANSYS 15.0. The design on this research was variaties with 4 designs that will compared and analysed demanding on immersed blade depth in water fluid flow. From the result of simulation the difference of water level shown flow structure different, which are the maximum pressure distribution and water velocity vector is at first condition (H = 880 mm) and the maximum blade force hit by water cause of potential energy is at (H = 880 mm) respectively 48.1 Pa (Static Pressure), 57.0 Pa (Total Pressure), 0.3479 m/s (Velocity Magnitude), 1.28 N (Blade 1), 11.47 N (Blade 2) and 18.42 N (Blade 3).Keywords: Low-Head, Immersed Blade Depth, Pressure Distribution, Velocity Vector, ANSYS Simulation.